A Case Study of Anorexia Nervosa Driven by Religious Sacrifice - Amelia A. Davis; Mathew Nguyen (Case Reports in Psychiatry)
Anorexia nervosa (AN) is considered a relatively “modern” disorder; however, a number of scholarly works have cited examples of voluntary self-starvation dating back to several centuries. In particular, there are many examples of female starvation for religious reasons during the medieval period, with many being elevated to sainthood. We present a case of an elderly woman with AN who began restricting her diet when she was 13-years old while studying to be a nun at a Catholic convent. She reports that, during the development of her disease, she had no mirrors and, rather than restricting her diet to be thin or attractive, she restricted her diet to be closer to God in hopes of becoming a Saint. This unique case presents an opportunity to deepen our understanding of AN and the cultural context that affects its development.